Pathophysiology of altitude adaptation - Monge M., Carlos (1956)
The basic position of the researcher in the case of adaptation to the height of the existing races since prehistoric times, must be established on the concept of acclimatization, the undisputed leading inherent ability to live and reproduce. Therefore, the problem statement involves studying altitude climates and biological characteristics of the beings that inhabit it; that is, the functional integration mechanisms between organism and environment. It is considered as a starting point, bioclimatic units constituting physiological systems in dynamic equilibrium adapted to live from sea level perhaps above 5,300 meters (Bowman), who may just be the ecumene of the human race.